Cannabis and its constituents for cancer: History, biogenesis, chemistry and pharmacological activities. (January 2021) - Lal, Samridhi; Shekher, Anusmita; Puneet,; Narula, Acharan S.; Abrahamse, Heidi; Gupta, Subash C.
Graphical abstract: Abstract: Cannabis has long been used for healing and recreation in several regions of the world. Over 400 bioactive constituents, including more than 100 phytocannabinoids, have been isolated from this plant. The non-psychoactive cannabidiol (CBD) and the psychoactive Δ 9 -tetrahydrocannabinol (Δ 9 -THC) are the major and widely studied constituents from this plant. Cannabinoids exert their effects through the endocannabinoid system (ECS) that comprises cannabinoid receptors (CB1, CB2), endogenous ligands, and metabolizing enzymes. Several preclinical studies have demonstrated the potential of cannabinoids against leukemia, lymphoma, glioblastoma, and cancers of the breast, colorectum, pancreas, cervix and prostate. Cannabis and its constituents can modulate multiple cancer related pathways such as PKB, AMPK, CAMKK-β, mTOR, PDHK, HIF-1α, and PPAR-γ. Cannabinoids can block cell growth, progression of cell cycle and induce apoptosis selectively in tumour cells. Cannabinoids can also enhance the efficacy of cancer therapeutics. These compounds have been used for the management of anorexia, queasiness, and pain in cancer patients. Cannabinoid based products such as dronabinol, nabilone, nabiximols, and epidyolex are now approved for medical use in cancer patients. Cannabinoids are reported to produce a favourable safety profile. However, psychoactive properties and poor bioavailability limit the use of some cannabinoids. The Academic Institutions across the globe are offering training courses on cannabis. How cannabis and its constituents exert anticancer activities is discussed in this article. We also discuss areas that require attention and more extensive research.